Influencia del marketing en redes sociales y de la promoción de ventas en las ventas digitales de las pequeñas empresas que comercializan productos orgánicos - Gálvez Rivera, Pamela Ana (2022)
This research consists of seven chapters. In the first chapter, we try to describe the problem of how to improve the digital sales of small companies that sell organic products. Also, there are the objectives, which are related to the mentioned problem. In the second chapter, the theoretical framework is detailed. It consists of research background, theoretical bases and components of the theoretical framework. It should be noted that the theoretical bases considered indispensable for the study were the 4C's theory of marketing, the marketing mix theory, and the supply and demand theory. In the third chapter, the hypotheses related to the problem to be solved are presented. In addition, the dependent variable "Digital sales" and the independent variables "Social media marketing" and "Sales promotion". The fourth chapter details the methodology used in the study. In addition, it shows the calculations of the sample used for this research work, which consisted of 76 organic small businesses in the department of Lima. The fifth chapter describes the results obtained in the study. You will be able to observe the graphs and their comments for each question of the instrument in order to interpret and guarantee an in-depth analysis. The sixth chapter shows the conclusions of the research based on the results obtained through the instrument. The last chapter contains recommendations for small businesses that sell organic products interested in improving their digital sales.